The test-induced warm-up effect on hamstring flexibility tests - Wootaek Lim (World Scientific Publishing, 2024)
Background: Although the effect of active warm-up (WU) on acute flexibility enhancement is well documented, the test-induced WU effect in muscle length test has not been widely studied. Objective: This study aimed to verify the test-induced WU effect on hamstring flexibility tests. Methods: The active knee extension (AKE) was performed using the right leg, whereas the straight leg raise (SLR) was performed using the left leg. Ten trials of AKE or SLR were performed: two as the pre-intervention trials (Pre); six as the WU intervention; and another two trials as the post-intervention (Post). During WU, subjects in the WO-Hold group performed six trials of the AKE or SLR without hold, and those in the W-Hold group performed six trials of the AKE or SLR with a 5[Formula: see text]s hold. Results: A significant difference was noted between Pre-AKE and Post-AKE, and between Pre-SLR and Post-SLR, respectively, in both the groups. The effect of WU is clear when performing consecutive AKE or SLR without any additional hold. Conclusion: Practitioners should be cautious in interpreting the testing result to avoid overestimation of the treatment effect since the test itself may induce substantial WU effect to the target tissues.